Chinese food security and climate change: Agriculture futures - Ye, Liming; Tang, Huajun; Wu, Wenbin; Yang, Peng; Nelson, Gerald C.; Mason-D’Croz, Daniel; Palazzo, Amanda (Kiel Institute for the World Economy, 2013)
Food security in China affects the livelihood and well-being of one-fifth of the world population. Climate change is now affecting agriculture and food production in every country of the world. Here the authors present the IMPACT model results on yield, production, and net trade of major crops (wheat, rice, and maize) in China, and on daily calorie availability as an overall indicator of food security under climate change scenarios and socio-economic pathways in 2050. The obtained results show that wheat, maize, and rice yields will increase by 17%, 45%, and 15%, alongside price increases of 60%, 100%, and 40%, respectively, during 2010-2050. Crop production is projected to increase by 23%, 70%, and 3% reaching 123, 240, and 125 million tons for wheat, maize, and rice, respectively, in 2050. The results also show that China will remain a major importer of maize at 20 million tons per year, but turn from a net importer of rice (5 million tons per year in 2010) to a net exporter in 2020 (5-9 million tons per year by 2050), while becoming a self-sufficient consumer of wheat by 2050. The outcomes of calorie availability suggest that China will be able to maintain a level of at least 3,000 kilocalories per day through 2010-2050. Climate change has relatively little effect on calorie availability within a pathway scenario.The authors conclude that Chinese agriculture is relatively resilient to climate change. Chinese food security by 2050 will unlikely be compromised in the context of climate change. The major challenge to food security, however, will rise from increasing demand coupled with regional disparities in the adaptive capacity to climate change.